Carboxymethyl cellulose - ammonium chloride on electrical of plasticized propylene carbonate solid bio-polymer electrolytes (SBPs) using experimental and computational studies - M. I. N. Isa; N. H. Ahmad (Taylor & Francis, 2024)
Volume: 193 Issue: 2